Observation of anti-PT-symmetry and higher-order exceptional point PT-symmetry in ternary systems for single-mode operation - Milad Jahangiri; Gholam-Mohammad Parsanasab; Leila Hajshahvaladi (Scientific Reports)
Abstract Nowadays, topological parity-time (PT) and anti- parity-time (APT) symmetry systems have attracted substantial attention due to their noticeable features and specific applications. The emergence of exceptional points in these systems plays a direct role in their overall responses and causes them to exhibit an entirely real spectrum. Here, we propose and analyze a new approach based on the broken PT in the vicinity of a third-order exceptional point and APT symmetry that allows us to experimentally achieve a stable single-mode laser. A feasible third-order exceptional point can be synthesized by coupling three microcavities to each other. The behaviors of these lasers are evaluated in different situations according to introducing the gain and loss perturbation to the system. Our proposed microlasers and their distinct properties based on photonic exceptional points may find use in a wide variety of applications such as ultrahigh precision sensing, spectroscopy, and optical on-chip filters and lasers.